PARENCANAAN KEBUTUHAN BAHAN BAKU SNPATU DENGAN METODE MATERIAL REQUIRI,MINT PLANNING (MRP) - Dyah Retno Purwatiningsih (Jurnal Teknik Industri, 2001)
IJD KartikaM agetanis a companyw hich produceo r assemblys hoesth at is activitiesdepend on the demand. This company doesn't have a good schedule in requirement andunschedulemd aterial.T his is becomesb y overloadm ateriacl apacitys o that increaseth e holdingcost a.ndr equirementc ost. To scheduleth e appropiatem aterial arriving we needt o plan materialavailabilityw ith Material RequiremenPt lanning( MRP). Firstly implementingt his methodforecast he dernandu, singl inier programmingm ethodt o makea gregata nd Masterp roductionSchedule (MPS). We need the data such as demand, product structure, component stock ,productionc apacitya, ndp roductionc ost.This methodg et the numbero f regulerw orkeri s about 13 personsH. oldingc ost afterimplemented MRP is about Rp 4.608.047,48 and before implemented MRp is aboutRp 6.455.677,08S. otherei s about P;,pl.847.629o,6t2 9% off afteru singM Rp method..